DNA Tetrahedron‐Enhanced Catalytic Hairpin Assembly for in Situ Monitoring of Viral RNA in Host Cells - Lu, Sha; Ma, Ai‐Xin; Gao, Xiao‐Lin; Dai, Zhi‐Qi; Li, Qing‐Nan; Liu, Yang‐Yang; Zhang, Yi; Meng, Qi; Pang, Dai‐Wen; Cui, Yun‐Xi; Kong, De‐Ming (Chemistry : a European journal, 2025)
Viruses pose significant threats to global public health and have substantial socio‐economic impacts. Developing rapid, sensitive, and specific in situ virus‐detection technologies is crucial for tracking viral genome release, replication in host cells, and intercellular transmission, thus holding great promise in understanding viral infection mechanisms, enabling early diagnosis, screening antiviral drugs, and formulating prevention and treatment strategies. In this study, we present a multifunctional tetrahedral DNA nanostructure (TDN)‐based system designed to monitor viral RNA levels in host cells in situ. The system employs a TDN‐based hyperbranched catalytic hairpin assembly (CHA) reaction to achieve rapid and powerful signal amplification, generating specific fluorescence resonance energy transfer (FRET) signals in response to target viral RNA. Using Japanese encephalitis virus (JEV) as a model, we developed the THA@JEV system responding to JEV‐RNA. This system demonstrated rapid and sensitive detection of JEV‐RNA within 12 minutes in a cell‐free environment, enabling real‐time imaging of JEV‐RNA in situ within host cells. The integrated TDN structure enhanced the biological stability of the probes and ensured their reliability under various stress conditions and microenvironments. This TDN‐based sensor system shows significant potential for elucidating viral infection pathways and advancing related virology research, as well as for screening antiviral drugs. A multifunctional system based on tetrahedral DNA nanostructures (TDN) for detecting and monitoring the release and replication of Japanese encephalitis virus (JEV) genomic RNA in host cells. The system responds to the presence of viral RNA, utilizing a highly efficient TDN‐based hyperbranched catalytic hairpin assembly to produce specific fluorescence resonance energy transfer (FRET) signals corresponding to the level of the target viral RNA.